2019
DOI: 10.21831/cp.v38i3.26411
|View full text |Cite
|
Sign up to set email alerts
|

Capturing Teaching Motivation of Teacher in the Disadvantaged Areas

Abstract: Teaching motivation of teachers is very important for student’s development. The purpose of this study is to test the teaching motivation of teachers in disadvantaged areas affected by the school climate and self-concept through the satisfaction of basic psychological needs. The subjects of this research were 241 teachers. Data collection techniques used instruments in the form of a school climate scale, a scale of self-concept, a scale of basic psychological need satisfaction, and a scale of teaching motivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 21 publications
0
11
0
2
Order By: Relevance
“…The results of this study are also supported by research findings Utami, Prestrigde, Saukah & Hamied (2019) that the development of professional teachers can be done by increasing attitudes of social psychology and good self-perception about the environment. This is also reinforced by the results of research by Utomo, Suminar, & Hamidah (2019) that satisfaction of basic psychological needs as an external factor is the result of the formation of teacher motivation in continuously increasing competence in teaching.…”
Section: Discussionmentioning
confidence: 84%
“…The results of this study are also supported by research findings Utami, Prestrigde, Saukah & Hamied (2019) that the development of professional teachers can be done by increasing attitudes of social psychology and good self-perception about the environment. This is also reinforced by the results of research by Utomo, Suminar, & Hamidah (2019) that satisfaction of basic psychological needs as an external factor is the result of the formation of teacher motivation in continuously increasing competence in teaching.…”
Section: Discussionmentioning
confidence: 84%
“…The principal is very supportive and motivates the teacher in the application of the picture and picture model because providing motivation and support for learning is very important. The resulting study of Utomo, H. B., Suminar, D. R., & Hamidah, H. (2019) teaching motivation is a result of the role of the school climate as an external factor and satisfaction of basic psychological needs and self-concept as an internal factor. In line with Pramudjono, P. (2015) found that motivation influences the teachers' commitment, meaning that the higher the motivation is, the higher the teachers' commitment is.…”
Section: Discussionmentioning
confidence: 99%
“…Yapılan araştırmalar (İhtiyaroğlu, 2017;Gün ve Turabik, 2019) öğretme motivasyonunu etkileyen birçok faktör olduğunu göstermektedir. Bunlardan biri okul iklimidir (Pretorius ve De Villiers, 2009;Utomo, Suminar ve Hamidah, 2019;Wei, 2012;Werang, 2018). Kocabaş'a (2009) göre olumlu okul iklimi oluşturmak, öğretmenleri öğretim etkinliklerinde öz gelişimlerini sağlamaları konusunda motive eder.…”
Section: Introductionunclassified